1995
DOI: 10.1099/13500872-141-7-1535
|View full text |Cite
|
Sign up to set email alerts
|

Variability in expression of antigens responsible for serotype specificity in Candida albicans

Abstract: The monoclonal antibody (mAb) B9E, which reacts with a cell wall surface determinant of Candida albicans serotype A, and a polyclonal monospecif ic antiserum against the antigen 6 (IF6) were used to investigate the expression of the antigens responsible for the serotype specificity in C. albicans under different growth conditions. By indirect immunofluorescence, both antibodies reacted with the cell wall surface of serotype A yeast cells and germ tubes grown in witm but no reactivity was observed with serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Conversely, studies performed with polyclonal antibodies from immunized or infected rabbits have shown that serotype B strains may gain factor 6 (specific for serotype A) in vivo and produce germ tubes that express antigen 6 (32). This observation was confirmed by using an MAb (2). Other experiments have shown that acellular extracts of serotype B cells contain enzymes (mannosyl transferases) required for the construction of serotype A epitopes (35).…”
supporting
confidence: 55%
“…Conversely, studies performed with polyclonal antibodies from immunized or infected rabbits have shown that serotype B strains may gain factor 6 (specific for serotype A) in vivo and produce germ tubes that express antigen 6 (32). This observation was confirmed by using an MAb (2). Other experiments have shown that acellular extracts of serotype B cells contain enzymes (mannosyl transferases) required for the construction of serotype A epitopes (35).…”
supporting
confidence: 55%
“…IFA was carried out as described previously (1). Briefly, the fungal species studied were grown on Sabouraud agar plates for 48 h at 24 or 37°C, resuspended in PBS at a cell density of 10 6 cells/ml, and placed on Tefloncoated immunofluorescence slides.…”
Section: Methodsmentioning
confidence: 99%
“…3B) (57). ␤-Mans are epitopes of anti-C. albicans polyclonal antibodies (63,74) and monoclonal antibodies (MAbs) with finely tuned specificity based on the ␤-Man chain length or the association with ␣-1,2-Mans (2,7,20,22,36,70). Some of these antibodies have been shown to be protective in experimental models of systemic or vaginal candidiasis (9,20,21).…”
mentioning
confidence: 99%